Acetate Downregulates the Activation of NLRP3 Inflammasomes and Attenuates Lung Injury in Neonatal Mice With Bronchopulmonary Dysplasia - Zhang, Qian; Ran, Xiao; He, Yu; Ai, Qing; Shi, Yuan (Frontiers in Pediatrics, 2021)
Background: Bronchopulmonary dysplasia (BPD) is a common pulmonary complication in preterm infants. Acetate is a metabolite produced by the gut microbiota, and its anti-inflammatory function is well known. The role of acetate in BPD has not been studied. Here, we investigate the effects of acetate on lung inflammation and damage in mice model of BPD. Objective: To investigate the role of acetate in the development of BPD. Methods: C57BL/6 mice were randomly divided into three groups on the 3rd day after birth: room air group, hyperoxia group, and hyperoxia + acetate (250 mM, 0.02 ml/g) group. The expression of inflammatory factors was determined by ELISA and RT-PCR, and NLRP3 and caspase-1 were detected by Western blot. High-throughput sequencing was used to detect bacterial communities in the mice intestines. Results: After acetate treatment, the expression levels of TNF-α, IL-1β, IL-18, NLRP3, and caspase-1 were significantly reduced, while the expression of GPR43 was increased. In the BPD mice treated with acetate, the proportion of Escherichia-Shigella was lower than in placebo-treated BPD mice, while the abundance of Ruminococcus was increased. Conclusions: These results indicate that acetate may regulate intestinal flora and reduce inflammatory reactions and lung injury in BPD. Therefore, acetate may be an effective drug to protect against neonatal BPD.